Interface elasticity effects in polymer-filled nanoporous metals. (February 2017) - Wilmers, J.; McBride, A.; Bargmann, S.
Abstract: A continuum formulation for electroactive composites made from nanoporous gold and ion-conducting polymer is proposed. A novel extension of surface elasticity theory is developed to account for the high surface-to-volume ratio of nanoporous gold, and to capture the chemoelectromechanical coupling that occurs on the interface between the metal and the polymer. This continuum formulation accounts for the fully non-linear behaviour exhibited by the composite. The balance of linear momentum, Gauß's flux theorem and a relation for the transport of charge carriers are introduced in the bulk material as well as on the interface to describe the non-linear multiphysics and highly coupled response of the actuator. The resulting system of non-linear equations is solved using the finite element method. A series of numerical examples is presented to elucidate the theory. Highlights: A novel continuum mechanical framework for electromechanical coupling is proposed. Interface effects are accounted for by an extension of interface elasticity. Model fully couples mechanical, electrostatic and diffusional behaviour. Numerical examples illustrate interaction of different electromechanical effects.